Controle robusto de manipuladores robóticos com juntas flexíveis - Nakamura, Marcelo Minoru Yamashita (2017)
This work consists of studying the robust control of robotic manipulators with flexible joints, specifically a planar and serial manipulator with two degrees of freedom and joint flexibility. The main objective of this study is to use a robust control technique called D-stability, to minimize the effects on certain variables of the system. The simulation of the robotic manipulator control system should provide a satisfactory performance for the system, even with modeling uncertainties present in the model representation of the plant. For this purpose, the concepts of Linear Matrix Inequalities (LMIs) will be used. The design of the controller will be based on the mathematical formulation of the dynamic model of the manipulator with flexible joints.